A geometric approach to harmonic color palette design. Issue 1 (2nd November 2018) - Lara‐Alvarez, Carlos; Reyes, Tania
Abstract: We address the problem of finding harmonic colors, this problem has many applications, from fashion to industrial design. The proposed approach enables the evaluations and generation of color combinations incrementally. To solve this problem, we consider that colors follow normal distributions in tone (chroma and lightness) and hue. The proposed approach relies in the International Commission on Illumination standard for representing colors and evaluates proximity. Other approaches to this problem use a set of rules. Experimental results show that lines with specific parameters—angles of inclination and distance from the reference point—are preferred over others and that uncertain line patterns outperform nonlinear patterns.